Energy consumption from hydropower in rural brazilian areas: sustainable vision - Remussi, Rejane; Biegelmeyer, Uiliam Hahn; Fernandes, Alice Munz; Craco, Tania; Motta, Marta Elisete Ventura da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Brazilian power industry currently is collapsing, where periods of high temperatures, water shortages and rising electricity consumption. Under a sustainable vision, promoting research and investment in new sources of electricity. Among these energy consumption categories, the countryside has high demand history, justifying the adoption of new technologies and modernization in agricultural production techniques, whose bias expansion demonstrates failure and unsustainable supply of electricity. The objective of this study was to describe the electricity sector, with the features and emphasis consumption of rural areas, which was proposed other sources of electricity. This research is characterized as exploratory and descriptive as its purpose, literature, and documents in relation to its procedures, presenting the history of electricity consumption by rural Brazil and its expansion bias, emphasizing hydroelectricity under a sustainable vision and proposing the adoption of wind energy and biomass as a sustainable source for electricity generation in rural areas.